1994
DOI: 10.1021/jm00034a005
|View full text |Cite
|
Sign up to set email alerts
|

New Dual Inhibitors of Neutral Endopeptidase and Angiotensin-Converting Enzyme: Rational Design, Bioavailability, and Pharmacological Responses in Experimental Hypertension

Abstract: In the treatment of cardiovascular diseases, it could be of therapeutic interest to associate the hypotensive effects resulting from the inhibition of angiotensin II formation, ensured by endothelial angiotensin-converting enzyme (ACE), with the diuretic and natriuretic responses due to the protection of the endogenous atrial natriuretic peptide (ANP) from inactivation by epithelial neutral endopeptidase (NEP). However, an investigation of this hypothesis requires an orally active compound able to jointly inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 30 publications
(65 reference statements)
2
71
0
Order By: Relevance
“…Introduction ofa methyl group in the f3 position ofthis residue led to the best superimposition with both the putative biologically active conformation ofthiorphan in the active site of NEP (36) and the constrained benzolactam II structure obtained from molecular modeling studies (48 In this study, a comparison between SHRs and the other models of hypertension showed that there was no difference for the hypotensive and the natriuretic response with RB 105 at 25 mg/kg in the different models. The natriuretic effect in the three models is likely to be related to NEP inhibition, and the hypotensive effect is probably due to NEP inhibition in deoxycortisone acetate-induced hypertensive rats but related to ACE inhibition in renovascular hypertensive rats (19).…”
Section: Discussionmentioning
confidence: 65%
“…Introduction ofa methyl group in the f3 position ofthis residue led to the best superimposition with both the putative biologically active conformation ofthiorphan in the active site of NEP (36) and the constrained benzolactam II structure obtained from molecular modeling studies (48 In this study, a comparison between SHRs and the other models of hypertension showed that there was no difference for the hypotensive and the natriuretic response with RB 105 at 25 mg/kg in the different models. The natriuretic effect in the three models is likely to be related to NEP inhibition, and the hypotensive effect is probably due to NEP inhibition in deoxycortisone acetate-induced hypertensive rats but related to ACE inhibition in renovascular hypertensive rats (19).…”
Section: Discussionmentioning
confidence: 65%
“…5,6 Single molecules that inhibit both the angiotensin-converting enzyme (ACE) and NEP (vasopeptidase inhibitors) have been developed in recent years. 7 Simultaneous inhibition of both ACE and NEP produces greater short-term and long-term benefits in experimental models of heart failure than does ACE inhibition alone. 8,9 Omapatrilat is a dual inhibitor of both ACE and NEP, which has been evaluated for the treatment of hypertension and heart failure.…”
mentioning
confidence: 99%
“…Key Words: hypertension, renal Ⅲ kidney failure Ⅲ angiotensin-converting enzyme Ⅲ peptides Ⅲ nitric oxide Ⅲ sodium, dietary V asopeptidase inhibitors are novel molecules that inhibit both angiotensin-converting enzyme (ACE) and neutral endopeptidase 24.11 (NEP). 1 The emergence of this new class of drugs followed the demonstration that ACE and NEP are 2 key enzymes that play a major role in regulating cardiovascular and renal functions. The simultaneous inhibition of these 2 enzymes can reduce the vasopressive, hypertrophic, and antinatriuretic activities of the renin-angiotensin system and potentiate the vasodilatory, natriuretic, and antiproliferative effects of bradykinin and natriuretic peptides.…”
mentioning
confidence: 99%
“…1 The emergence of this new class of drugs followed the demonstration that ACE and NEP are 2 key enzymes that play a major role in regulating cardiovascular and renal functions. The simultaneous inhibition of these 2 enzymes can reduce the vasopressive, hypertrophic, and antinatriuretic activities of the renin-angiotensin system and potentiate the vasodilatory, natriuretic, and antiproliferative effects of bradykinin and natriuretic peptides.…”
mentioning
confidence: 99%